A cellulose nanocrystal film with iridescent humidity indication and wet writing function, and its preparation method and application

By mixing the cellulose nanocrystal colloidal suspension with xylose and nano zinc oxide, forming a film and drying, a cellulose nanocrystal film with iridescent humidity indication and wetting writing functions was prepared, which solved the problem of easy folding and fragile cellulose nanocrystal film, and achieved efficient humidity sensing and writing functions.

CN117209822BInactive Publication Date: 2025-04-08NANJING FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311306966.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing cellulose nanocrystal films are easy to fold and fragile, have poor mechanical and ductile properties, and are difficult to achieve iridescent humidity indication and wet writing functions.

Method used

By mixing the cellulose nanocrystalline colloidal suspension with xylose and nanozinc oxide, and forming a film to dry it, a cellulose nanocrystalline film with iridescent humidity indication and wetting writing functions was prepared.

Benefits of technology

The prepared cellulose nanocrystal film has sensitive humidity sensing function and wetable writing function, presenting visible or polarized iridescent, which is stable, environmentally friendly and sustainable, and is used in the fields of environmental humidity sensing, fiber and textiles, architectural decoration, printing, color writing and display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117209822B_ABST
    Figure CN117209822B_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose nanocrystal film with iridescent color humidity indication and wet writing functions, a preparation method and application thereof, and belongs to the technical field of cellulose film preparation. The method mixes a cellulose nanocrystal colloidal suspension, xylose and nano zinc oxide, and then forms a film of the mixed solution, and dries it to obtain a cellulose nanocrystal film. The cellulose nanocrystal film prepared by the invention has a sensitive humidity sensing function and a wet writing function, presents visible iridescence or polarized iridescence, is stable, environmentally friendly and sustainable, and has good applications in the fields of environmental humidity sensing fibers and textiles, architectural decoration, printing, color writing and display.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cellulose film preparation, and in particular relates to a cellulose nanocrystal film with iridescent humidity indication and wet writing functions, and a preparation method and application thereof. Background Art

[0002] Cellulose is the main component of wood fiber biomass and is the most abundant renewable green resource on earth. It mainly comes from the cell walls of cotton, wood or grass plants, and presents a multi-layered aggregate structure and a two-phase structure containing ordered crystalline regions and disordered non-crystalline regions. The unique structural characteristics of cellulose give it huge application potential.

[0003] Cellulose, as the structural backbone of plants, is the most abundant natural polymer in the world. Cellulose nanocrystals (CNC) can be extracted from cellulose. It is a sustainable, renewable and biodegradable emerging nanomaterial that has received widespread attention in recent years due to its unparalleled chemical and mechanical properties. Cellulose nanocrystals are highly crystalline (crystallinity is 54% to 88%) rod-shaped particles, about 3 to 5 nm wide and about 50 to 500 nm long. They have unique chemical and mechanical properties, such as high aspect ratio, low density, high stiffness and low thermal expansion coefficient, which are not possessed by traditional cellulose-derived materials. CNC has extremely high strength, even exceeding that of steel products. CNC is widely used in pharmaceuticals, fibers and textiles, and drug delivery. Cellulose nanocrystal films have a wide range of applications. For example, chitosan and cellulose nanocrystals can form a green and tunable oxygen barrier layer through self-assembly, and have shown broad application prospects in the field of food and drug packaging. In addition, cellulose nanocrystals can be used as fillers to form composite films with nanocomposites to improve the strength and stiffness of the composites. Since the successful preparation of dense CNC films can provide a substrate with a large surface area, laying a good foundation for its application in the fields of pharmaceuticals, drug delivery, biosensors, solar cells, etc., it is of great significance to study the preparation of CNC films.

[0004] The cellulose polymer chain consists of a two-phase structure consisting of a crystalline region and an amorphous region. CNC refers to the rod-shaped crystal formed by removing the less stable and amorphous non-crystalline region. It has stronger structural rigidity, better modifiability, and broad application potential. The rod-shaped structure of nanocellulose has high strength, large modulus, and large specific surface area, which is conducive to material preparation. The material prepared by introducing CNC not only has better mechanical properties, but also interacts with polymers to form covalent bonds or non-covalent bonds to further enhance its flexibility and ductility. Nanocellulose itself can also be processed by chemical and physical modification to give it better utilization performance and improve its application potential. Using the liquid crystal behavior of CNC suspension, it can be prepared into a new type of film material, which can provide new methods and new ideas for multifunctional printing, 3D printing, etc.; using the iridescence phenomenon of CNC liquid crystal phase, the prepared film can be used for optical filters, sensors, etc.; further adding functional molecular additives can also enable CNC films to achieve intelligent applications such as environmental stimulus response.

[0005] CNC has high rigidity, so the nanocellulose film obtained by its natural evaporation usually shows a brittle and fragile morphology, poor mechanical properties and ductility. Improving the flexibility, ductility and other mechanical properties of the film formed by CNC through compounding and modification methods is an important prerequisite for its wide application. Therefore, it is urgent to solve the problems of CNC being brittle and fragile, and having poor mechanical properties and ductility, and to prepare a film with greater polarized light filtering performance than ordinary cellulose film. Summary of the invention

[0006] In view of the above-mentioned problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for preparing a cellulose nanocrystal film with iridescent color humidity indication and wet writing functions, and to prepare a cellulose nanocrystal film with sensitive humidity sensing function and wet writing function. The second technical problem to be solved by the present invention is to provide a cellulose nanocrystal film with iridescent color humidity indication and wet writing functions, which has sensitive humidity sensing function and wet writing function, presents visible iridescence or polarized iridescence, and is stable, environmentally friendly and sustainable. The third technical problem to be solved by the present invention is to provide a cellulose nanocrystal film with iridescent color humidity indication and wet writing functions for use in the fields of environmental humidity sensing fibers and textiles, architectural decoration, printing, color writing and display.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a cellulose nanocrystal film with iridescent color humidity indication and wet writing functions comprises mixing a cellulose nanocrystal colloidal suspension, xylose (Xyl) and nano zinc oxide (ZnO NPs), then forming a film from the mixed solution and drying it to obtain the cellulose nanocrystal film.

[0009] Furthermore, the concentration of the cellulose nanocrystal colloidal suspension is 0.8% to 1.5%.

[0010] Furthermore, the mass ratio of the cellulose nanocrystals, xylose and nano zinc oxide is 100:20:1-5.

[0011] Furthermore, the mass ratio of the cellulose nanocrystals, xylose and nano zinc oxide is 100:20:1.25-5.

[0012] Furthermore, the crystallinity of the cellulose nanocrystal film is 65% to 80%.

[0013] Furthermore, the crystallinity of the cellulose nanocrystal film is 70% to 75%.

[0014] Further, the specific steps are as follows:

[0015] 1) adding softwood pulp to 60% sulfuric acid at 55°C, mechanically stirring at 400 rpm for 1.5 hours, diluting the solution to four times of the original volume, centrifuging and rinsing three times, and then dialyzing in deionized water for 7 days until the pH reaches 6, and finally ultrasonicating for 30 minutes to prepare a cellulose nanocrystal colloidal suspension with a concentration of 0.8% to 1.5%;

[0016] 2) adding xylose and nano zinc oxide to the cellulose nanocrystal colloidal suspension prepared in step 1) and mixing, and then magnetically stirring at room temperature for 6 hours;

[0017] 3) Forming the mixed solution stirred in step 2) into a film and drying it to obtain a cellulose nanocrystal film.

[0018] Furthermore, the method prepares a cellulose nanocrystal film.

[0019] Furthermore, the cellulose nanocrystal film is used in the fields of environmental humidity sensing fibers and textiles, architectural decoration, printing, color writing and display.

[0020] Furthermore, the color writing is applied in a fountain pen writing board.

[0021] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0022] (1) The cellulose nanocrystal film prepared by the present invention has sensitive humidity sensing function and wettable writing function, presents visible iridescence or polarized iridescence, is stable, environmentally friendly and sustainable, and has good applications in the fields of environmental humidity sensing fibers and textiles, architectural decoration, printing, color writing and display.

[0023] (2) The present invention can fully regulate the iridescent color of the CNC film by changing the type and proportion of additives, thereby preparing CNC iridescent films containing different colors.

[0024] (3) The iridescent structural color of the CNC iridescent film prepared by the present invention will change under different humidity conditions, presenting different colors.

[0025] (4) The CNC iridescent film prepared by the present invention has a crystallinity of 69% to 76% and has good flexibility and tensile strength.

[0026] (5) The CNC iridescent film prepared by the present invention can be applied to writing functions, which is novel, rapid, accurate and repeatable compared with other materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The iridescence phenomenon and polarized light microscope image of CNC and its composite film prepared by the present invention, the scale bar is 100 μm;

[0028] Figure 2 The XRD spectra of the composite films with different Xyl and ZnO NPs addition amounts of the present invention;

[0029] Figure 3 This is a diagram showing rapid changes in iridescence color of the CNC-3 film prepared in Example 4 of the present invention under water vapor humidity control;

[0030] Figure 4 This is a demonstration of the text writing encryption anti-counterfeiting application of the CNC-2 film prepared in Example 3 of the present invention;

[0031] Figure 5 A comparison chart of the tensile properties of the CNC film prepared in Example 1 of the present invention and the CNC-5 film prepared in Example 6;

[0032] Figure 6 The CNC film prepared in Example 1 of the present invention is demonstrated for text writing application. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments.

[0034] Example 1

[0035] Preparation of Cellulose Nanocrystal Film (CNC):

[0036] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 hours; the suspension was diluted to four times of the original volume, centrifuged and rinsed, and repeated three times; the sample was dialyzed in deionized water for 7 days until the pH reached 6, and finally ultrasonically treated for 30 minutes to prepare a uniform CNC colloidal suspension with a concentration of 1.04% for standby use;

[0037] (2) The CNC colloidal suspension prepared in step (1) was magnetically stirred at room temperature, marked as CNC, for 6 h.

[0038] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0039] This example represents sample CNC, and the crystallinity of the film is 87.9%.

[0040] Example 2

[0041] Preparation of cellulose nanocrystal film (CNC-1):

[0042] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 h. The suspension was diluted to four times of its original volume and centrifuged for three times. The sample was then dialyzed in deionized water for 7 days until the pH reached 6 and then ultrasonically treated for 30 min to prepare a uniform CNC colloidal suspension with a concentration of 1.04%.

[0043] (2) Weigh Xyl and mix it with the prepared CNC colloidal suspension with a concentration of 1.04%, wherein the mass ratio of cellulose nanocrystals to Xyl is 100:20, marked as CNC-1, and the prepared mixed solution is magnetically stirred at room temperature for 6 hours.

[0044] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0045] This example represents sample CNC-1, and the crystallinity of the CNC-1 film is 76.5%.

[0046] Example 3

[0047] Preparation of cellulose nanocrystal film (CNC-2):

[0048] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 h. The suspension was diluted to four times of its original volume and centrifuged for three times. The sample was then dialyzed in deionized water for 7 days until the pH reached 6 and then ultrasonically treated for 30 min to prepare a uniform CNC colloidal suspension with a concentration of 1.04%.

[0049] (2) Weigh Xyl and ZnO NPs (particle size of 5-10 nm) and mix them with the prepared CNC colloidal suspension with a concentration of 1.04%. The mass ratio of cellulose nanocrystals, Xyl and ZnO NPs is 100:20:1, marked as CNC-2, and the prepared mixed solution is magnetically stirred at room temperature for 6 hours.

[0050] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0051] This example represents sample CNC-2, and the crystallinity of the CNC-2 film is 74.3%.

[0052] Example 4

[0053] Preparation of cellulose nanocrystal film (CNC-3):

[0054] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 h. The suspension was diluted to four times of its original volume and centrifuged for three times. The sample was then dialyzed in deionized water for 7 days until the pH reached 6 and then ultrasonically treated for 30 min to prepare a uniform CNC colloidal suspension with a concentration of 1.04%.

[0055] (2) Weigh Xyl and ZnO NPs (particle size of 5-10 nm) and mix them with the prepared CNC colloidal suspension with a concentration of 1.04%. The mass ratio of cellulose nanocrystals, Xyl and ZnO NPs is 100:20:1.25, marked as CNC-3, and the prepared mixed solution is magnetically stirred at room temperature for 6 hours.

[0056] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0057] This example represents sample CNC-3, and the crystallinity of the CNC-3 film is 71.0%.

[0058] Example 5

[0059] Preparation of cellulose nanocrystal film (CNC-4):

[0060] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 h. The suspension was diluted to four times of its original volume and centrifuged for three times. The sample was then dialyzed in deionized water for 7 days until the pH reached 6 and then ultrasonically treated for 30 min to prepare a uniform CNC colloidal suspension with a concentration of 1.04%.

[0061] (2) Weigh Xyl and ZnO NPs (particle size of 5-10 nm) and mix them with the prepared CNC colloidal suspension with a concentration of 1.04%. The mass ratio of cellulose nanocrystals, Xyl and ZnO NPs is 100:20:2.5, marked as CNC-4, and the prepared mixed solution is magnetically stirred at room temperature for 6 hours.

[0062] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0063] This example represents sample CNC-4, and the crystallinity of the CNC-4 film is 70.5%.

[0064] Example 6

[0065] Preparation of cellulose nanocrystal film (CNC-5):

[0066] (1) About 8 g of softwood pulp sample was added to 400 mL of 60% sulfuric acid at 55°C and mechanically stirred at 400 rpm for 1.5 h. The suspension was diluted to four times of its original volume and centrifuged for three times. The sample was then dialyzed in deionized water for 7 days until the pH reached 6 and then ultrasonically treated for 30 min to prepare a uniform CNC colloidal suspension with a concentration of 1.04%.

[0067] (2) Weigh Xyl and ZnO NPs (particle size of 5-10 nm) and mix them with the prepared CNC colloidal suspension with a concentration of 1.04%. The mass ratio of cellulose nanocrystals, Xyl and ZnO NPs is 100:20:5, marked as CNC-5, and the prepared mixed solution is magnetically stirred at room temperature for 6 hours.

[0068] (3) The homogeneous suspension obtained above was cast into three culture dishes with a diameter of 30 mm and a capacity of 8.0 mL, and naturally evaporated and air-dried at room temperature for 4 to 7 days to form a composite film. The evaporated and dried film was collected with pointed tweezers for subsequent characterization.

[0069] This example represents sample CNC-5, and the crystallinity of the CNC-5 film is 72.2%.

[0070] Figure 1 The iridescence phenomenon and polarizing microscope images of the CNC and its composite film prepared by the present invention. It can be seen from the figure that the CNC film prepared by the present invention has a regular chiral nematic structure, so it appears as a detailed iridescence in macroscopic observation, and the iridescence is different when the addition amounts of Xyl and ZnO NPs are different, which is controllable.

[0071] Figure 2 The XRD spectra of the composite films with different Xyl and ZnO NPs addition amounts of the present invention show that when the addition ratio of nano zinc oxide increases, the crystallinity of the obtained CNC composite film decreases to 70%, indicating that the brittleness of the film is reduced and the toughness is enhanced, which is beneficial to its later application.

[0072] Example 7

[0073] Test of rainbow color humidity indication function:

[0074] The CNC-3 film sample was used as the experimental group. It was placed 10 cm above the water vapor. The changes in its iridescent structural color were observed and recorded by the naked eye. It was found that the color of the film changed rapidly, from the shorter wavelength blue-green to the longer wavelength light green and orange-red at 5s, 10s, 15s, and 20s, respectively. The pitch gradually increased and changed to the longer wavelength light green and orange-red. This phenomenon may be due to the rapid embedding of water molecules into the chiral nematic structure of the CNC-3 film nanocrystal at high temperature, which expanded its intermolecular hydrogen bonds and increased the pitch. Therefore, its reflection wavelength increased and the iridescent color showed a rapid red shift. This macroscopic optical change can be directly determined by the naked eye or semi-quantitatively measured by UV-Vis, which can greatly broaden its application range. At the same time, the film's sensitivity to humidity in this experiment is significantly higher than that of other environmental humidity sensors, and it has a wide range of application potential in environmental monitoring, humidity sensing and other fields.

[0075] The nanocomposite films made by combining ZnO NPs and Xyl as additives with cellulose nanocrystals also showed higher flexibility and tensile strength than pure nanocellulose films. By changing the type and proportion of additives, CNC iridescent films containing different colors can be prepared.

[0076] Figure 3 This is a diagram showing the rapid change of iridescence color of the CNC-3 film prepared in Example 4 of the present invention under water vapor humidity control; as can be seen from the figure, the film changes color within 5 to 20 seconds, reflecting extremely sensitive humidity sensing performance.

[0077] Example 8

[0078] Application of wet writing function:

[0079] Based on the above characteristics of rapid response to environmental humidity, the CNC-2 sample was assembled to form a new type of water pen writing board with rapid display and disappearance functions. "CNC" was written on the sample with a fine brush dipped in water, and the film writing board changed color rapidly, successfully recording the written content. The written film sample was air-dried at room temperature. After the water dried, it can be directly observed that the written "CNC" disappeared and the iridescent film returned to its original state. This phenomenon is mainly due to the fact that the water molecules embedded in the chiral nematic structure exist mainly in the form of free water around the CNC rod-shaped crystals. After air drying, they evaporate and disappear. The rod-shaped crystals restore their original spiral arrangement structure due to their intermolecular hydrogen bonds and electrostatic effects, and the pitch is close to the original state, so the reflected iridescent color wavelength is similar and the color is the same.

[0080] Figure 4 This is a diagram showing the text writing encryption anti-counterfeiting application of the CNC-2 film prepared in Example 3 of the present invention; as can be seen from the figure, due to its humidity responsiveness, after writing with a fountain pen, it changes color, thereby being able to display text, and as it dries naturally, the text disappears and the film returns to its original state, showing certain application potential in the field of anti-counterfeiting encryption.

[0081] Example 9

[0082] Comparison of tensile properties of CNC and CNC-5 films, such as Figure 5 shown.

[0083] Figure 5 This is a comparison chart of the tensile properties of the CNC film prepared in Example 1 of the present invention and the CNC-5 film prepared in Example 6. It can be seen from the figure that the tensile properties of CNC are weak and the toughness is poor. Its elongation at break is 1.1% and its maximum tensile strength is 12 MPa. However, due to the introduction of Xyl and ZnO NPs, the elongation at break of CNC-5 increases to 1.7% and the maximum tensile strength is increased to 27 MPa.

[0084] Comparative Example 1

[0085] Assemble the CNC samples and conduct the water pen writing board experiment. Use a fine brush dipped in water to write "CNC" on the sample. Figure 6 shown.

[0086] Figure 6 The CNC film prepared in Example 1 of the present invention is demonstrated for text writing application. As can be seen from the figure, due to the absence of Xyl and ZnO NPs, the film has poor mechanical properties and insufficient hydrophobicity. Although there is a color change, the film is wetted and broken, and repeated writing cannot be achieved.

[0087] Comparative Example 2

[0088] According to online searches, the chiral nematic films reported in this patent and other papers have advantages. In the article "Microstructure and Humidity Response Behavior of Polyethylene Glycol / Cellulose Nanocrystal Composite Liquid Crystal Film" (Journal of Zhejiang A&F University, 2023, 40(X): 1–7), polyethylene glycol was introduced to increase the toughness of CNC, but its tensile strength was 12-16Mpa, and the tensile force enhancement effect did not reach the result of this patent, and it did not show the humidity-sensitive rewritable performance. Although the article "Preparation of Antistatic Cellulose Nanocrystal Rainbow Anti-counterfeiting Label Film" (PACKAGING ENGINEERING, Vol. 38, No. 9, May 2017, Nanjing Forestry University, Wan Xuan, Zhang Yayun, Sun Yufei, Li Dagang) also introduced the metal oxide Fe3O4, it only increased the antistatic properties of the CNC film material, and there was no detailed optimization effect in terms of iridescent color display, humidity response indication and mechanical performance improvement.

Claims

1. A method for preparing a cellulose nanocrystal film with iridescent humidity indication and wet writing function, characterized in that: A cellulose nanocrystal colloidal suspension, xylose and nano zinc oxide are mixed, and then the mixed solution is formed into a film and dried to obtain a cellulose nanocrystal film; wherein the mass ratio of the cellulose nanocrystals, xylose and nano zinc oxide is 100:20:1-5; the crystallinity of the cellulose nanocrystal film is 65%-80%; and the concentration of the cellulose nanocrystal colloidal suspension is 0.8%-1.5%.

2. The method for preparing the cellulose nanocrystal film with iridescent humidity indication and wet writing function according to claim 1, characterized in that: The mass ratio of the cellulose nanocrystals, xylose and nano zinc oxide is 100:20:1.25-5.

3. The method for preparing the cellulose nanocrystal film with iridescent humidity indication and wet writing function according to claim 1, characterized in that: The crystallinity of the cellulose nanocrystal film is 70% to 75%.

4. The method for preparing the cellulose nanocrystal film with iridescent humidity indication and wet writing function according to claim 1, characterized in that: The specific steps are as follows: 1) Add softwood pulp to 60% sulfuric acid at 55°C and stir mechanically at 400 rpm for 1.5 h. After stirring, dilute the solution to four times of its original volume, centrifuge and rinse three times, and then dialyze in deionized water for 7 days until the pH reaches 6. Finally, ultrasonicate for 30 min to prepare a 0.8% to 1.5% cellulose nanocrystal colloidal suspension. 2) adding xylose and nano zinc oxide to the cellulose nanocrystal colloidal suspension prepared in step 1) and mixing, and then magnetically stirring at room temperature for 6 hours; 3) Forming the mixed solution stirred in step 2) into a film and drying it to obtain a cellulose nanocrystal film.

5. The cellulose nanocrystal film prepared by the method according to any one of claims 1 to 4.

6. Application of the cellulose nanocrystal film according to claim 5 in the fields of environmental humidity sensing fibers and textiles, architectural decoration, printing, color writing and display.

7. The use according to claim 6, characterized in that: The color writing is applied in a fountain pen writing board.

Citation Information

Patent Citations

  • Preparation method of nanocellulose liquid crystal paper with optical limiting characteristic

    CN113045787A

  • Microparticles of cellulose nanocrystals with pigment nanoparticles bound thereto and method of production thereof

    US20220040053A1